Historia de los Papas desde fines de la Edad Media En la época de la monarquía absoluta - PASTOR, Ludovico (G.GILI, 1952)
Contenido : INOCENCIO XI; 1676-1689; ALEJANDRO VIII; 1689-1691; INOCENCIO XII; 1691-1700